A new-generation internal tide model based on 30 years of satellite sea surface height measurements: multiwave decomposition and isolated beams - Z. Zhao; Z. Zhao (Earth System Science Data)
An internal tide model, ZHAO30yr, is developed using 30 years of satellite altimetry sea surface height (SSH) measurements from 1993 to 2022 by a recently improved mapping technique that consists of two rounds of plane wave analysis with a spatial bandpass filter in between. Prerequisite wavelengths are calculated using climatological annual mean hydrographic profiles in the World Ocean Atlas 2018. ZHAO30yr only extracts the 30-year phase-locked internal tide component, lacking the incoherent component caused by the time-varying ocean environment. The model contains 12 internal tide constituents: eight mode-1 constituents (M2, S2, N2, K2, K1, O1, P1, and Q1) and four mode-2 constituents (M2, S2, K1, and O1). Model errors are estimated to be lower than 1 mm in the SSH amplitude on global average, thanks to the long data record and improved mapping technique. The model is evaluated by making internal tide correction to independent altimetry data for 2023. A total of 10 constituents (but for K2 and Q1) can reduce variance on global average. K2 and Q1 can only cause variance reductions in their source regions. The model decomposes the multiconstituent, multimodal, multidirectional internal tide field into a series of simple plane waves at each grid point. The decomposition reveals unprecedented features previously masked by multiwave interference. The model divides each internal tide constituent into components by propagation direction. The directionally decomposed components show numerous long-range internal tidal beams associated with notable topographic features. The semidiurnal internal tidal beams off the Amazon shelf and the diurnal internal tidal beams in the Arabian Sea are examined in detail. ZHAO30yr is available at https://doi.org/10.6084/m9.figshare.28078523 (Zhao, 2024b). Model errors are available at https://doi.org/10.6084/m9.figshare.28559978.v3 (Zhao, 2025).